2010
DOI: 10.1007/s13193-010-0012-z
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node mapping in early breast cancer — Our experience

Abstract: Background The axillary lymph node status is the most important determinant of prognosis in patients with breast cancer. Sentinel lymph node (SLN) biopsy is a safe alternative for axillary clearance with an equal efficacy limiting the morbidity caused by axillary clearance.Patient and methods From May 1996 till September 2009, 523 clinically node negative, early breast cancer patients attending our clinic at All India Institute of Medical Sciences were included in the study. They underwent sentinel lymph node … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…6,16 However, if both techniques or only radioactive dye was used, the sentinel node detection rates and accuracy of the procedure ranged from 86 to 98% and 97.5 to 98%, respectively. 6,[11][12][13][14][15][16][17][18][19][20] In previous reported studies, the sensitivity of the procedure of SNB was 88 to 89% when only blue dye was used compared with 92.2 to 94.2% when both techniques were utilized. 13,15 Studies have reported hypersensitivity to isosulfan blue dye at rates of 1 to 2%.…”
Section: Discussionmentioning
confidence: 99%
“…6,16 However, if both techniques or only radioactive dye was used, the sentinel node detection rates and accuracy of the procedure ranged from 86 to 98% and 97.5 to 98%, respectively. 6,[11][12][13][14][15][16][17][18][19][20] In previous reported studies, the sensitivity of the procedure of SNB was 88 to 89% when only blue dye was used compared with 92.2 to 94.2% when both techniques were utilized. 13,15 Studies have reported hypersensitivity to isosulfan blue dye at rates of 1 to 2%.…”
Section: Discussionmentioning
confidence: 99%
“…The other patient had undergone previous surgery which could have disrupted lymphatic drainage to the axillary nodes. Therefore, tumor size, localization, previous surgery could have negative effects on the accuracy of the SLN biopsy [ 27 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The patients scheduled for surgery were injected with radioactive isotope Tc99m-tagged sulphur colloid of 200-300 microcurie in 0.1-0.2 mL normal saline in sub-areolar region 1-3 h before surgery. 31 Radiotracer was injected in the afternoon, a day before surgery, if the patient was scheduled as first case next day morning. A gamma-detecting probe was used intra-operatively to identify radioactivity positive nodes.…”
Section: Identification and Excision Of Sentinel Lymph Nodementioning
confidence: 99%